Elder abuse in New Zealand : social risk factors : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology in Psychology at Massey University, Manawatu, New Zealand - Woodhead, Yvonne (Massey University, 2018)
Elder abuse is a single or repeated act, or lack of appropriate action, occurring within any relationship where there is an expectation of trust which causes harm or distress to an older person. Elder abuse has been linked to significant morbidity and mortality and is receiving increasing attention from policymakers and health professionals. The research literature has identified various factors as correlates of elder abuse. Given the strength of evidence for loneliness and lack of social support as correlates of elder abuse, the present study aimed to examine these factors as well as a related concept, social network type, in the New Zealand context. Data was analysed from the 2010 and 2012 waves of the New Zealand Longitudinal Study of Ageing (NZLSA) which focused on health and ageing indicators such (𝘕 = 3277 in 2010; 𝘕 = 3212 in 2012). Cross-sectionally, the focus of this study was whether loneliness, social support and social network type predicted elder abuse. Longitudinally, I explored whether the same three variables predicted later elder abuse at two-year follow-up. Multiple regression, moderation and mediation analyses were primarily applied. Elder abuse was found to be related to poorer physical and mental health outcomes both at baseline and two years later. Loneliness and social support were both related to elder abuse, with loneliness also related to elder abuse two years later. Social network type was not related to elder abuse. Social support had a moderating effect on the relationship between elder abuse and loneliness as well as a partially mediating effect on the relationship between elder abuse and mental health. Loneliness partially mediated the relationships between elder abuse and lower physical health, lower mental health and increased age. Most of these moderating and mediating effects were significant both at baseline and two years later. Potential limitations and suggestions for future research are discussed. These findings are intended to provide supporting evidence that loneliness and social support are key factors to consider as correlates of elder abuse, and to inform health professionals, researchers and older adults about social lifestyle choices likely to reduce risk of elder abuse.
Keywords: Older people -- Abuse of -- New Zealand -- Risk factors; Older people -- Abuse of -- New Zealand -- Prevention; Abused elderly -- Services for -- New Zealand; Social work with older people -- New Zealand